Using a situational awareness global assessment technique for interprofessional obstetrical team training with high fidelity simulation. Issue 1 (January 2015) - Morgan, Pamela; Tregunno, Deborah; Brydges, Ryan; Pittini, Richard; Tarshis, Jordan; Kurrek, Matt; DeSousa, Susan; Ryzynski, Agnes
Abstract Evidence suggests that breakdowns in communication and a lack of situation awareness contribute to poor performance of medical teams. In this pilot study, three interprofessional obstetrical teams determined the feasibility of using the situation awareness global assessment technique (SAGAT) during simulated critical event management of three obstetrical scenarios. After each scenario, teams were asked to complete questionnaires assessing their opinion of how their performance was affected by the introduction of questions during a SAGAT stop. Fifteen obstetrical professionals took part in the study and completed the three scenarios in teams consisting of five members. At nine questions per stop, more participants agreed or strongly agreed that there were too many questions per stop (57.1%) than when we asked six questions per stop (13%) and three questions per stop (0%). A number of interprofessional differences in response to this interprofessional experience were noted. A team SAGAT score was determined by calculating the proportion of correct responses for each individual. Higher scores were associated with better adherence to outcome times, although not statistically significant. A robust study design building on our pilot data is needed to probe the differing interprofessional perceptions of SAGAT and the potential association between its scores and clinical outcome times.